Preparation of a graphite phase carbon nitride-based composite photocatalyst and application thereof in synthesis of hydrogen peroxide
Patent Information
- Application Number
- CN202411313352.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
但是作为单组份催化剂,它仍具有光生载流子易复合、光吸收能力较弱等缺点
本发明所制备的最佳催化剂在较宽pH范围内表现出良好的适应性,且在碱性环境下光催化合成的过氧化氢优于酸性环境下,并且过氧化氢的产量在pH 3-10的范围内没有太大改变。此外,对于所合成的最佳催化剂能够在碱性条件下高效地合成过氧化氢。
Smart Images

Figure CN119140144B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalysis technology, specifically relating to the preparation of a graphite-phase carbon nitride-based composite photocatalyst and its application in the synthesis of hydrogen peroxide. Background Technology
[0002] With the development of modern industry, energy crises and environmental pollution have become increasingly serious problems. Energy shortages and environmental degradation are among the major issues facing humanity in the 21st century and urgently need to be addressed. Therefore, the utilization of new energy sources and the control of environmental pollution are of great significance to the national sustainable development strategy. Hydrogen peroxide (H2O2), as an environmentally friendly green chemical, has seen its market demand increase year by year and is widely used in environmental protection, petrochemical, electronics, and food industries. However, traditional methods for preparing hydrogen peroxide are energy-intensive, require expensive equipment, involve complex processes, pose certain safety hazards during production, and easily generate harmful byproducts. Therefore, finding a low-cost, clean, and safe synthetic method for preparing hydrogen peroxide is urgently needed.
[0003] However, the synthesis of hydrogen peroxide using traditional methods presents several challenges. For instance, the anthraquinone process consumes large amounts of organic matter, while electrochemical methods require high-concentration salt electrolytes and additional energy and equipment input. Photocatalysis offers a more promising approach. Driven by solar energy, this method can reduce oxygen through photogenerated electrons, utilizing ubiquitous oxygen and water to synthesize hydrogen peroxide—a clean, green, and sustainable method. Furthermore, graphitic carbon nitride (g-C3N4) has garnered significant attention since its application in photocatalytic water splitting in 2009. It is an n-type semiconductor with a band gap of approximately 2.7 eV, capable of absorbing photons with wavelengths less than 460 nm. Compared to traditional TiO2, it offers a wider spectral absorption range, is easier to prepare with less demanding equipment requirements, and has a shorter preparation time. Additionally, g-C3N4 is non-toxic, environmentally friendly, and produces no secondary pollution. However, as a single-component catalyst, it still suffers from drawbacks such as easy recombination of photogenerated carriers and relatively weak light absorption. Summary of the Invention
[0004] In view of the problems existing in the prior art, the purpose of this invention is to provide a preparation method for a graphitic carbon nitride-based composite photocatalyst and its application in the synthesis of hydrogen peroxide. The composite photocatalyst prepared by this invention exhibits a wide light absorption range and effective carrier separation efficiency across the entire wavelength range, thus demonstrating a good photocatalytic synthesis rate of hydrogen peroxide. The preparation method of this invention is simple, uses widely available raw materials, is safe and environmentally friendly, and has low equipment requirements.
[0005] The method for preparing the graphite-phase carbon nitride-based composite photocatalyst of the present invention involves the thermal polymerization of melamine and sodium tripolyphosphate at high temperature, and includes the following steps: Melamine and sodium tripolyphosphate were ground in a mortar and mixed evenly. The mixture was then transferred to a boat-shaped ceramic crucible and placed in a tube furnace. The furnace was calcined at 450–560 °C for 1–3 hours under a N2 atmosphere. After calcination, the resulting solid product was ground into powder, washed several times with deionized water and ethanol, and finally dried overnight at 60 °C to obtain Na-CN(N2).
[0006] The mass ratio of melamine to sodium tripolyphosphate is 3:1-3, the calcination temperature is 450-560℃, and the holding time is 1-3h.
[0007] Furthermore, the mass ratio of melamine to sodium tripolyphosphate is 3:2.
[0008] Furthermore, the calcination temperature is 520℃, the heating rate is 5℃ / min, and the holding time is 2 h.
[0009] The present invention relates to the application of graphite-phase carbon nitride-based composite photocatalysts in the synthesis of hydrogen peroxide.
[0010] The specific steps are as follows: Using deionized water and isopropanol as a mixed solvent, add the graphite-phase carbon nitride-based composite photocatalyst and disperse it evenly. Then, transfer the mixed solution to a photocatalytic reactor, stir under light-proof and sealed conditions, without introducing additional oxygen, and react under xenon lamp irradiation (light intensity 120 mW / cm²). 2 Hydrogen peroxide was obtained by (with wavelength covering the entire wavelength range).
[0011] Furthermore, the preferred catalyst mass to solvent volume ratio is 1:1250 (g / mL); in addition, the xenon lamp provides full-spectrum irradiation.
[0012] In the mixed solvent, the volume ratio of deionized water to isopropanol is 9:1.
[0013] The pH value of the catalytic reaction system is 3-10, preferably 7-10.
[0014] The beneficial effects of this invention are as follows: The optimal catalyst prepared in this invention exhibits good adaptability over a wide pH range, and the photocatalytic synthesis of hydrogen peroxide is superior under alkaline conditions compared to acidic conditions, with the hydrogen peroxide yield remaining largely unchanged within the pH range of 3-10. Furthermore, the optimal catalyst synthesizes hydrogen peroxide efficiently under alkaline conditions.
[0015] This invention employs a simple calcination method to prepare a graphitic carbon nitride-based composite photocatalyst, which enables the efficient synthesis of H₂O₂ via photocatalytic reaction across the entire wavelength range without oxygen exposure (light intensity 120 mW / cm²). 2The wavelength was measured across the entire wavelength range. The catalyst dosage was 0.8 g / L. The reaction system consisted of 45 mL of deionized water and 5 mL of isopropanol in a 100 mL beaker (without additional oxygen introduction). After 3 h of reaction, the yield reached 12.3 mmol / L. The optimal ratio of components in the catalytic material was obtained through effective control of the composite photocatalyst synthesis process and testing of its photocatalytic H2O2 production performance.
[0016] The material prepared by this invention is produced by thermal polymerization of melamine and sodium tripolyphosphate at high temperature. The method is simple, the operation process is straightforward, it is easy to expand, and it can be prepared on a large scale. It is used as a photocatalyst in the photocatalytic production of hydrogen peroxide, exhibiting high photocatalytic activity and good stability. Attached Figure Description
[0017] Figure 1 X-ray powder diffraction patterns of CN, Na-CN1.0(N2), and Na-CN1.0(Air).
[0018] Figure 2 Scanning electron microscope images of CN(a), Na-CN1.0(N2)(b), and Na-CN1.0(Air)(c).
[0019] Figure 3 Transmission electron microscope images of CN(a), Na-CN1.0(N2)(b), and Na-CN1.0(Air)(c).
[0020] Figure 4 The UV-Vis diffuse reflectance spectra are for CN, Na-CN1.0 (N2), and Na-CN1.0 (Air).
[0021] Figure 5 Electrochemical impedance spectroscopy for CN, Na-CN1.0(N2), and Na-CN1.0(Air).
[0022] Figure 6 The photoluminescence spectra of CN, Na-CN1.0(N2) and Na-CN1.0(Air) are shown.
[0023] Figure 7 Fourier transform infrared spectra of CN, Na-CN1.0(N2), and Na-CN1.0(Air).
[0024] Figure 8 The graph shows the hydrogen peroxide synthesis rate of Na-CN1.0(N2) under different calcination temperatures across the entire wavelength range.
[0025] Figure 9 The graph shows the hydrogen peroxide synthesis rate of Na-CN1.0(N2) across the entire wavelength range under different heat preservation times.
[0026] Figure 10 The graph shows the hydrogen peroxide synthesis rate across the entire wavelength range for different catalyst ratios.
[0027] Figure 11 The synthesis rates of hydrogen peroxide from CN, Na-CN1.0 (N2), and Na-CN1.0 (Air) are plotted across the entire wavelength range.
[0028] Figure 12 The synthesis rates of hydrogen peroxide from CN, Na-CN1.0 (N2), and Na-CN1.0 (Air) under visible light and across the entire wavelength range are plotted.
[0029] Figure 13 The graph shows the synthesis rates of Na-CN1.0 (N2) and hydrogen peroxide at different pH values.
[0030] Figure 14 pH values of Na-CN1.0(N2) suspensions with different concentrations of NaOH added (initially pH=8). Detailed Implementation
[0031] To make the technical objectives, technical solutions, and beneficial effects of the present invention clearer, the technical solutions of the present invention will be further described below with reference to specific examples, but the scope of protection of the present invention is not limited thereto.
[0032] Example 1: Preparation of CN
[0033] 1.5 g of melamine was ground in a mortar for 20 minutes, mixed thoroughly, and then transferred to a boat-shaped ceramic crucible. The crucible was placed in a tube furnace and heated to 520°C at a rate of 5°C / min under a nitrogen atmosphere, and held for 2 hours. After the reaction was complete, the calcined material was transferred back to a mortar and ground into powder. This powder was then transferred to a 250 mL beaker, and 100 mL of water was added and stirred for 5 hours. After the reaction was complete, the powder was centrifuged, the precipitate was collected, and repeatedly washed with water. Finally, the solid precipitate was placed in a 60°C oven and dried for 24 hours to obtain CN.
[0034] Example 2: Preparation of Na-CN1.0 (N2) 1.5 g of melamine and 1.0 g of sodium tripolyphosphate were ground in a mortar for 20 minutes until homogeneous. The mixture was then transferred to a boat-shaped ceramic crucible and placed in a tube furnace. Under a N2 atmosphere, the temperature was increased to 520°C at a rate of 5°C / min and held for 2 hours. After the reaction was complete, the calcined material was transferred back to the mortar and ground into powder. The powder was then transferred to a 250 mL beaker, and 100 mL of water was added. The mixture was stirred for 5 hours. After the reaction was complete, the mixture was centrifuged, and the precipitate was collected. The precipitate was washed repeatedly with water, and finally, the solid precipitate was placed in a 60°C oven and dried for 24 hours to obtain Na-CN1.0(N2).
[0035] Example 3: Preparation of Na-CN1.0(N2)-X 1.5 g of melamine and 1.0 g of sodium tripolyphosphate were ground in a mortar for 20 minutes until homogeneous. The mixture was then transferred to a boat-shaped ceramic crucible and placed in a tube furnace. Under a N2 atmosphere, the temperature was increased to 450℃, 480℃, 520℃, and 560℃ at a heating rate of 5℃ / min, and held for 2 h. After the reaction was complete, the calcined material was transferred back to the mortar and ground into powder. The powder was then transferred to a 250 mL beaker, and 100 mL of water was added and stirred for 5 h. After the reaction was complete, the mixture was centrifuged, the precipitate was collected, and washed repeatedly with water. Finally, the solid precipitate was placed in a 60℃ oven and dried for 24 h to obtain Na-CN1.0(N2)-X. X represents different temperatures.
[0036] Example 4: Preparation of Na-CN1.0(N2)-Y 1.5 g of melamine and 1.0 g of sodium tripolyphosphate were ground in a mortar for 20 minutes until homogeneous. The mixture was then transferred to a boat-shaped ceramic crucible and placed in a tube furnace. Under a N2 atmosphere, the temperature was increased to 520°C at a rate of 5°C / min and held for 1 h, 2 h, and 3 h, respectively. After the reaction was complete, the calcined material was transferred back to the mortar and ground into powder. The powder was then transferred to a 250 mL beaker, and 100 mL of water was added. The mixture was stirred for 5 h. After the reaction was complete, the mixture was centrifuged, and the precipitate was collected. The precipitate was washed repeatedly with water, and finally, the solid precipitate was placed in a 60°C oven and dried for 24 h to obtain Na-CN1.0(N2)-Y. Y represents different time intervals.
[0037] Example 5: Preparation of Na-CN(N2)-Z 1.5 g of melamine and Z g of sodium tripolyphosphate were ground in a mortar for 20 minutes until homogeneous. The mixture was then transferred to a boat-shaped ceramic crucible and placed in a tube furnace. Under a N2 atmosphere, the temperature was increased to 520°C at a rate of 5°C / min and held for 2 hours. After the reaction was complete, the calcined material was transferred back to the mortar and ground into powder. The powder was then transferred to a 250 mL beaker, and 100 mL of water was added. The mixture was stirred for 5 hours. After the reaction was complete, the mixture was centrifuged, and the precipitate was collected. The precipitate was washed repeatedly with water, and finally, the solid precipitate was placed in a 60°C oven and dried for 24 hours to obtain Na-CN(N2)-Z. Z represents the mass of sodium tripolyphosphate.
[0038] Example 6: Preparation of Na-CN1.0(Air)
[0039] 1.5 g of melamine and 1.0 g of sodium tripolyphosphate were ground in a mortar for 20 minutes until homogeneous. The mixture was then transferred to a crucible and heated to 520 °C in a muffle furnace for 2 h. After the reaction was complete, the calcined material was transferred back to the mortar and ground into powder. The powder was then transferred to a 250 mL beaker, and 100 mL of water was added and stirred for 5 h. After the reaction was complete, the mixture was centrifuged, the precipitate was collected, and washed repeatedly with water. Finally, the solid precipitate was placed in a 60 °C oven and dried for 24 h to obtain Na-CN1.0(Air).
[0040] Performance testing:
[0041] Figure 1 X-ray powder diffraction patterns of CN, Na-CN1.0(N2), and Na-CN1.0(Air) photocatalysts are shown. The results indicate that pure g-C3N4 exhibits different diffraction peaks at 13.1° and 27.7°, which are attributed to the (100) and (002) crystal planes of graphitic carbon nitride, respectively, and to the interlayer order of tris-s-triazine units and the interlayer stacking of conjugated aromatics, respectively. For the modified Na-CN1.0(N2) and Na-CN1.0(Air) samples, the main phase structure of graphitic carbon nitride changes. The figures show that both samples exhibit diffraction peaks of sodium metaphosphate, which may be due to the high-temperature decomposition of sodium tripolyphosphate.
[0042] Figure 2 Scanning electron microscope (SEM) images of CN(a), Na-CN1.0(N2)(b), and Na-CN1.0(Air)(c) show significant CN aggregation, exhibiting an irregular blocky structure with a rough and uneven surface. Na-CN1.0(Air) displays a long, rod-like structure, while Na-CN1.0(N2), as shown in the figure, exhibits a more pronounced three-dimensional structure, formed by a series of irregularly protruding rice-like structures arranged in an alternating pattern.
[0043] Figure 3 Transmission electron micrographs of CN(a), Na-CN1.0(N2)(b), and Na-CN1.0(Air)(c) can be seen. CN exhibits an irregular blocky structure with uneven distribution and easy stacking. Na-CN1.0(Air) shows a cuboid-like stacked structure, while Na-CN1.0(N2) shows a thinner layered stacked structure.
[0044] Figure 4The figures show the UV-Vis diffuse reflectance spectra of CN, Na-CN1.0(N2), and Na-CN1.0(Air). The figures reveal that, compared to CN and Na-CN1.0(Air), Na-CN1.0(N2) exhibits a significant increase in the maximum absorption edge and a red shift in the absorption margin, indicating a marked broadening of the catalyst's light absorption range. Furthermore, the absorption in the 480-900 nm region of the Na-CN1.0(N2) sample is also slightly improved, which can be attributed to the n–π* transition of lone pair electrons at the –C≡N defect sites. This enhanced adsorption capacity improves the utilization of photogenerated carriers and enhances photocatalytic performance.
[0045] Figure 5 Electrochemical impedance spectroscopy (EIS) plots for CN, Na-CN1.0(N2), and Na-CN1.0(Air) are shown. The plots reveal that the radii of curvature of CN and Na-CN1.0(Air) are smaller than those of Na-CN1.0(N2), indicating that their impedance values are also smaller. This suggests that Na-CN1.0(N2) exhibits better conductivity, indicating that the catalyst possesses superior charge transfer and separation capabilities.
[0046] Figure 6 The photoluminescence spectra of CN, Na-CN1.0(N2), and Na-CN1.0(Air) are shown. The photoluminescence (PL) signal intensity gradually decreases from Na-CN1.0(Air) to Na-CN1.0(N2), indicating that the increase in the content of -C≡N groups can effectively promote the separation of electrons and holes. This is because -C≡N groups have the property of accepting electrons and can absorb photogenerated electrons, thus facilitating the separation and transport of photogenerated electron-hole pairs.
[0047] Figure 7 Fourier transform infrared (FTIR) spectra of CN, Na-CN1.0 (N2), and Na-CN1.0 (Air). The figures show that all catalysts exhibit peak performance at 810 cm⁻¹. -1 1150-1800 cm -1 and 3000-3400 cm -1 Typical characteristic peaks exist between them, with the 810cm peak being the most prominent. -1 The sharp characteristic peaks are attributed to the out-of-plane bending characteristic peaks of the carbon-nitrogen triazine ring structure unique to carbon nitride, 1150-1800 cm⁻¹. -1 The series of peak widths between these points represent the CN stretching vibrations of the NC=N carbon-nitrogen heterocycle, ranging from 3000 cm⁻¹. -1 and 3400 cm -1 The broader characteristic peaks between these peaks are attributed to the stretching vibrations of NH. Furthermore, a notable difference is the peak at 2165 cm⁻¹. -1At this position, the signal from the cyano group (-C≡N) converted from the terminal -C-NH2 is stronger for Na-CN1.0(N2), and the presence of more cyano groups may help enhance visible light absorption, charge separation, and transfer to improve photocatalytic performance. Furthermore, due to the incorporation of phosphate, at 994 cm⁻¹... -1 The signal of OP was observed at 1071 cm. -1 The corresponding infrared peak is a PN bond.
[0048] Figure 8 The graph shows the hydrogen peroxide synthesis rate of Na-CN1.0(N2) under different calcination temperatures across the entire wavelength range, with a holding time of 2 h. As can be seen from the graph, the hydrogen peroxide synthesis performance first increases and then decreases with the increase of calcination temperature, and the best effect is achieved at a calcination temperature of 520℃.
[0049] Figure 9 The graph shows the hydrogen peroxide synthesis rate of Na-CN1.0(N2) across the entire wavelength range under different holding times, with a calcination temperature of 520℃. As can be seen from the graph, the hydrogen peroxide synthesis performance first increases and then decreases with increasing holding time, reaching its optimal effect after 2 hours of holding.
[0050] The synthesis performance of different catalyst ratios across the entire wavelength range was investigated at the optimal calcination temperature and optimal holding time. Figure 10 As shown in the figure, when the amount of melamine is kept constant at 1.5 g, the performance of photocatalytic synthesis of hydrogen peroxide shows a trend of first increasing and then decreasing with the addition of sodium tripolyphosphate. The performance of photocatalytic synthesis of hydrogen peroxide reaches its best when the mass of added sodium tripolyphosphate is 1 g.
[0051] Figure 11 The effect of photocatalytic preparation of hydrogen peroxide from CN, Na-CN1.0 (N2), and Na-CN1.0 (Air) under light (using a xenon lamp as the light source with a light intensity of 120 mW / cm²). 2 The wavelength was measured across the entire wavelength range, and the catalyst dosage was 40 mg. The reaction system consisted of 45 mL of deionized water and 5 mL of isopropanol in a 100 mL beaker (without additional oxygen introduced). As shown in the figure, after 3 hours of reaction, the hydrogen peroxide concentration in the solution of Na-CN1.0(N2) reached 12.3 mmol / L, while the concentrations of CN and Na-CN1.0(Air) were only 1.6 mmol / L and 5.3 mmol / L, respectively. The hydrogen peroxide production rate of Na-CN1.0(N2) was significantly higher than that of CN and Na-CN1.0(Air), indicating that it possesses the optimal photocatalytic hydrogen peroxide production performance.
[0052] Figure 12The figure compares the synthesis rates of hydrogen peroxide from CN, Na-CN1.0 (N2), and Na-CN1.0 (Air) under visible light and across the entire wavelength range. As can be seen from the figure, the synthesis rate of hydrogen peroxide from the catalyst under the entire wavelength range is much higher than that under visible light, which also shows that ultraviolet light plays an indispensable role in the production of hydrogen peroxide by the catalyst.
[0053] Furthermore, to highlight the advantages of the catalyst prepared in this invention, the synthesis rate of hydrogen peroxide from Na-CN1.0(N2) at different pH values was tested. The results are presented by... Figure 13 As can be seen, unlike other reports where the efficiency of catalysts in synthesizing H2O2 was inhibited in alkaline environments, Na-CN1.0(N2) exhibited good adaptability over a wide pH range, with H2O2 production remaining largely unchanged within the pH range of 3-10. Furthermore, Na-CN1.0(N2) was able to efficiently synthesize hydrogen peroxide over a wide pH range.
[0054] Proton donor capacity is assessed by increasing the pH of the suspension through the addition of sodium hydroxide (NaOH) to monitor proton consumption. Figure 14 As shown, when 2.5 and 10 mM NaOH are added, the pH value of the NaCN1.0(N2) suspension increases between 0.6 and 0.9, indicating that NaCN1.0(N2) has excellent proton donor ability, which is one of the reasons why NaCN1.0(N2) can synthesize H2O2 superiorly under alkaline conditions.
[0055] The above are merely preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be considered as limitations on the present invention, and the scope of protection of the present invention should be determined by the scope defined in the claims. For those skilled in the art, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. The application of a graphitic carbon nitride-based composite photocatalyst in the synthesis of hydrogen peroxide, characterized in that: Using deionized water and isopropanol as a mixed solvent, a graphitic carbon nitride-based composite photocatalyst was added and dispersed evenly. The mixed solution was then transferred to a photocatalytic reactor, stirred under light-proof and sealed conditions, without introducing additional oxygen, and reacted under xenon lamp irradiation to obtain hydrogen peroxide. The pH value of the catalytic reaction system is 3-10; The graphitic carbon nitride-based composite photocatalyst was prepared by a method comprising the following steps: Melamine and sodium tripolyphosphate were ground in a mortar and mixed evenly. The mixture was then transferred to a boat-shaped ceramic crucible and placed in a tube furnace for calcination. After calcination, the resulting solid product was ground into powder, washed with deionized water and ethanol, and dried to obtain Na-CN(N2). The calcination process is carried out in a nitrogen atmosphere at a temperature of 450-560℃ and a holding time of 1-3 hours. The mass ratio of melamine to sodium tripolyphosphate is 3:1-3.
2. The application according to claim 1, characterized in that: The calcination temperature was 520℃, and the holding time was 2 hours.
3. The application according to claim 1, characterized in that: The mass ratio of melamine to sodium tripolyphosphate is 3:
2.
4. The application according to claim 1, characterized in that: The illumination wavelength is the full wavelength range.
Citation Information
Patent Citations
Sodium doped graphite phase carbon nitride prepared by one-step synthesis and application thereof
CN106582765A
Photocatalysis catalyst, and preparation method and application thereof
CN112958130A